2012
DOI: 10.1111/j.1743-6109.2011.02595.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hypoactive Sexual Desire Disorder in Premenopausal Women: Efficacy of Flibanserin in the DAISY Study

Abstract: In premenopausal women with HSDD, flibanserin 100 mg once daily was well tolerated and associated with statistically significant improvements in SSE, sexual desire (FSFI desire domain score but not eDiary desire score), sexual function, and decrease in sexual distress vs. placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(142 citation statements)
references
References 21 publications
6
130
0
6
Order By: Relevance
“…Flibanserin, a drug purportedly acting as a 5-HT 1A receptor agonist and 5-HT 2A receptor antagonist, has been shown to increase paracopulatory behavior in female rats (Gelez et al, 2013) and it has been reported to have weak stimulatory effects on sexual motivation in women (DeRogatis et al, 2012;Thorp et al, 2012). These observations suggest that effects on paracopulatory behavior in rats indeed coincide with clinical effects in women.…”
Section: Paracopulatory Behavior As Indicator Of Female Sexual Motivamentioning
confidence: 81%
“…Flibanserin, a drug purportedly acting as a 5-HT 1A receptor agonist and 5-HT 2A receptor antagonist, has been shown to increase paracopulatory behavior in female rats (Gelez et al, 2013) and it has been reported to have weak stimulatory effects on sexual motivation in women (DeRogatis et al, 2012;Thorp et al, 2012). These observations suggest that effects on paracopulatory behavior in rats indeed coincide with clinical effects in women.…”
Section: Paracopulatory Behavior As Indicator Of Female Sexual Motivamentioning
confidence: 81%
“…When desire was measured by the FSFI desire domain, the results consistently showed statistically significant increases in desire versus placebo (an increase of 0.3 over placebo, the scale ranges from 1.2 to 6.0). The pivotal study outcomes including SSEs, FSFI desire domain scores, and Female Sexual Distress Scale (subscale related to distress about low desire) are summarized in Table 2 [14][15][16][17].…”
Section: Clinical Efficacymentioning
confidence: 99%
“…In the first two trials abbreviated as DAISY and VIOLET, flibanserin was found to have significant improvement in the number of sexually satisfying events, albeit with a marginal magnitude. 8,9 There was also improvement in other secondary end points such as FSFI, FSDS and item-13 scores. However the sexual desire score as assessed by eDiary score which was one of the co-primary end points did not reach statistical significance.…”
Section: Efficacymentioning
confidence: 92%